Some techniques in the correction of pupils’ mistakes and mispronunciations of lexical ‘‘en’’ in the dictation lesson - NKAM’DEY, KANEFU (Éducation et développement, 2017)
L’étude s’est déroulée dans les classes de 5ème et 6ème secondaires de quelques écoles de Kikwit. Cet article suggère quelques techniques appropriées d’enseignement, susceptibles d’aider les enseignants d’anglais en 5ème et 6ème secondaires à corriger les fautes des élèves, dues à la mauvaise prononciation et orthographe du lexical « en » observés pendant les leçons de dictée. La méthode d’observation systématique a permis de relever les fautes commises par les élèves dans la prononciation et l’orthographe de lexical « en». La technique documentaire a servi de recenser, collectionner et proposer les techniques susceptibles de résoudre ce problème d’enseignement d’une langue aussi importante qu’est l’anglais. Abstract The study took place in the 5th and 6th secondary classes of some Kikwit schools. This article suggests some appropriate teaching techniques, which can help teachers of English in 5th and 6th secondary to correct the mistakes of students, due to the bad pronunciation and spelling of lexical "en" observed during dictation lessons. The systematic observation method made it possible to identify the mistakes made by the pupils in the pronunciation and spelling of lexical "en". The documentary technique served to identify, collect and propose techniques that could solve this problem of teaching a language as important as English.